2008
DOI: 10.1111/j.1553-2712.2008.00178.x
|View full text |Cite
|
Sign up to set email alerts
|

A Double‐blind Randomized Clinical Trial Evaluating the Analgesic Efficacy of Ketorolac versus Butorphanol for Patients with Suspected Biliary Colic in the Emergency Department

Abstract: Objectives: Patients presenting to the emergency department (ED) with suspected biliary colic often require intravenous (IV) analgesia. The choice of IV analgesia typically includes opioids and ketorolac.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…This formulation could potentially be used in the future to treat circumscribed pruritus and thus avoid systemic side-effects. Adverse effects of butorphanol are, for example, dizziness, sedation and nausea (64,74). As with other morphine-like agents, respiratory depression can occur that is reversible in healthy subjects with moderate doses (up to 0.8 mg) of naloxone (64).…”
Section: Butorphanolmentioning
confidence: 99%
“…This formulation could potentially be used in the future to treat circumscribed pruritus and thus avoid systemic side-effects. Adverse effects of butorphanol are, for example, dizziness, sedation and nausea (64,74). As with other morphine-like agents, respiratory depression can occur that is reversible in healthy subjects with moderate doses (up to 0.8 mg) of naloxone (64).…”
Section: Butorphanolmentioning
confidence: 99%
“…However, a major systematic review was not selectively focused on visceral pain [243]. Multiple studies have found that NSAIDs are effective for biliary colic and are as effective as opioids with fewer side effects [244–247]. One of the mechanisms by which NSAIDs work in renal or biliary colic may involve acetylcholine blockade.…”
Section: Pharmacologic Management Of Visceral Painmentioning
confidence: 99%
“…Olsen et al[9] carried out a prospective randomized controlled trial comparing the efficacy of ketorolac vs butorphanol for patients with suspected biliary colic in the emergency department. This was a compact study with a definite aim (though limited by a small sample size) which concluded that both agents can be considered reasonable options in patients presenting with biliary colic, especially those with a need for further investigations.…”
Section: Resultsmentioning
confidence: 99%